183k views
2 votes
This is simplifying algebraic expressions, i want to know how you do this and can you show the steps so i understand better? Thanks!

This is simplifying algebraic expressions, i want to know how you do this and can-example-1

1 Answer

5 votes

Answer:

1) 12 - 4m

2) -10 - 15b

3) 44r - 30

4) -23 +21g

5) 10y

6) -5x - 10

7) -13r - 1

8) 11g - 7

9) 6n

10) -18n - 12

Explanation:

Note:

a) Simplification is making sure that the expression can no longer be worked on.

b) "Minus * Minus = Plus" , "Plus * Plus = Plus" and "Minus * Plus = Minus"

c) Like terms are terms that are of the same type

1) 7 - 4m + 5

collect like terms

= (7+5) - 4m

= 12 - 4m

2) -5(2 + 3b)

Multiply each term by -5

= -10 - 15b

3) 4r - 5(-8r + 6)

open the bracket by multiplying each term in the bracket by -5

= 4r + 40r - 30

collect like terms

= 44r - 30

4) -3(9-7g) + 4

open the bracket by multiplying each term in the bracket by -3

= -27 + 21g + 4

collect like terms

= -23 +21g

5) 9y + y

both terms are alike

∴ 10y

6) -9x - 2 - 8 + 4x

collect like terms

= -9x + 4x - 2 - 8

= -5x - 10

7) -6r - 7r - 9 + 8

collecting the like terms

= -13r - 1

8) 6g + 5g - 7

Collecting like terms

= 11g - 7

9) 7n - n

both are like terms

= 6n

10) 6(-3n - 2)

Open the bracket by multiplying each term by 6

= -18n - 12

User Radleybobins
by
6.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.